2014
DOI: 10.1186/s12865-014-0056-x
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae ghosts (VCG) exert immunomodulatory effect on dendritic cells for enhanced antigen presentation and induction of protective immunity

Abstract: BackgroundWe previously showed that the Vibrio cholerae ghost platform (VCG; empty V. cholerae cell envelopes) is an effective delivery system for vaccine antigens promoting the induction of substantial immunity in the absence of external adjuvants. However, the mechanism by which these cell envelopes enhance immunity and stimulate a predominantly Th1 cellular and humoral immune response has not been elucidated. We hypothesized that the immunostimulatory ability of VCG involves dendritic cell (DC) activation.O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…Culture of rPmp18.1 with BMDC resulted in the upregulated DC expression of MHC II and co-stimulatory molecules as well as TLR4 and intracellular NLRP3. These findings confirm the results of our previous studies reporting that inactivated chlamydial whole cell and subunit antigens stimulate the in vitro maturation of DCs (Eko et al, 2014 ; Pan et al, 2015 ). Engagement of CD40 on APCs has been demonstrated to lead to the up-regulated expression of MHC-II and CD80 and CD86n and production of inflammatory cytokines, such as TNF-α and IL-12 (Diehl et al, 2000 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Culture of rPmp18.1 with BMDC resulted in the upregulated DC expression of MHC II and co-stimulatory molecules as well as TLR4 and intracellular NLRP3. These findings confirm the results of our previous studies reporting that inactivated chlamydial whole cell and subunit antigens stimulate the in vitro maturation of DCs (Eko et al, 2014 ; Pan et al, 2015 ). Engagement of CD40 on APCs has been demonstrated to lead to the up-regulated expression of MHC-II and CD80 and CD86n and production of inflammatory cytokines, such as TNF-α and IL-12 (Diehl et al, 2000 ).…”
Section: Discussionsupporting
confidence: 92%
“…A combination of CpG and FL used as a mucosal adjuvant was shown to enhance the immune responses of co-delivered antigens (Fukuyama et al, 2011 ; Asanuma et al, 2012 ). In addition, the Vibrio cholerae ghost (VCG) platform has been demonstrated to be an effective immunomodulator for both subunit and inactivated chlamydial antigens (Eko et al, 2014 ). VCG are empty bacterial cell envelopes derived from V. cholerae cells by protein E-mediated lysis.…”
Section: Introductionmentioning
confidence: 99%
“…Determination of concentrations of Chlamydia specific antibody isotypes, Immunoglobulin (Ig) IgG and IgG 2c , in vaginal lavage of ECD or control mice were measured by standard ELISA procedure described previously 13 , 69 . Briefly, 96-well microtiter plates (Nunc Life Technologies, Rochester, NY) were coated with 20 µg/ml of chlamydial antigen (i.e., UV-inactivated C. muridarum elementary bodies) in 50 µl of PBS at 4 °C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Assessment of the ability of lysed JOL1950 cells to prime immature DCs, which are potent antigen-presenting cells, was used to evaluate the efficacy of the vaccine against Salmonella infection, since mature DCs differentiate by engulfing foreign proteins. It has been reported that BG produced by the expression of the PhiX174 lysis gene results in strong activation of DCs [ 44 , 45 ]. Major antigenic components preserved on BG, which are referred to as pathogen-associated molecular patterns (PAMPs), are recognized by toll-like receptors (TLRs) and other pathogen recognition receptors (PRRs), resulting in activation of mature DCs and subsequent induction of T-cell-related immune responses.…”
Section: Discussionmentioning
confidence: 99%